Virginija Vasiliauskienė, Kristina Rutkovska, Konstantino Sirvydo Punktai sakymų - Gelumbeckaitė, Jolanta (Baltistica, 2018)
–
Keywords: Altilitauisch; Konstantinas Sirvydas; Punktai sakymų; Rezension